Percentage expression of neutrophil activation marker in the peripheral blood of patients with dry eye disease plus type 2 diabetes (Ukrainian Journal of Ophthalmology, 2025)
Background: Dry eye disease (DED) is a disorder of the anterior segment of the eye which is common in patients with type 2 diabetes mellitus (T2DM). It has been reported that symptoms of DED were observed in 60-70% of patients with T2DM. Given that inflammation has a key role in the progression of both T2DM and DED, we believe it is reasonable to study the role of neutrophils in this process.Purpose: To assess the percentage expression of CD15, a neutrophil activation marker, in the peripheral blood of patients with both DED and T2DM.Material and Methods: Forty-six patients (92 eyes; mean age, 54.0 ± 8.0 years) with both DED and T2DM were included in this study. There were 19 (40%) women and 27 (60 %) men. Mean diabetes duration was 8.0 ± 6.6 years. All patients had well-compensated diabetes. In addition to a routine examination of the eye, Schirmer I test and tear film break-up time (TBUT) test, they had their corneal fluorescein staining (CFS) scored using the Oxford schema, severities of dry eye graded according to the DEWS II classification and Ocular Surface Disease Index (OSDI) obtained. An immunohistocytochemical study was employed to assess the expression of CD15, a neutrophil activation marker, in peripheral blood cells of patients.Results: The mean percentage expression of CD15, a neutrophil activation marker, in the peripheral blood, was 46.7% for 14 patients with T2DM plus DED and punctuate keratopathy, and 28.5% for 32 patients with T2DM plus DED and intact cornea (р=0.0001). There was a mild negative correlation between the expression of CD15 and the Schirmer score (r = -0.32; р = 0.032), and between the former and the TBUT score (r = -0.34; р = 0.019).
Keywords: type 2 diabetes mellitus; dry eye disease; neutrophil activation marker